Sosialisasi Pengendalian Hama dan Penyakit Tanaman (HPT) Berbasis Pertanian Organik Dalam Mendukung Ekonomi Hijau di Desa Tumbuh Mulia - Tsani, M.Khairul; Puspa Kinasih, Aulia; Darmasari Wahyuni, Elisa; Baburroziqin; Hasanah, Maratun; Putri Siti Soleha, Baiq; Bunayya Harakil Adzkar, Lalu; Firdaus, Moh.Firman; Liatul Ukmatul Jannah, Baiq; Adekayanti, Fajliani; Supeno, Bambang (Universitas Mataram, 2025)
Organic farming in Indonesia is gaining more attention as a sustainable alternative toaddressing environmental and health challenges. The decline in agricultural landproductivity and environmental degradation have driven the developments of organicfarming systems. Organic farming can serve as a safer alternative system as itproduces products free from synthetic chemical contaminants while also preservingenvironmental sustainability. The outreach activities on organic plant pest anddiseases (PPD) control in Tumbuh Mulia Village aim to support the development ofgreen economy. PPD control prioritizes an approach that integrates various methodsthat manage pest populations while considering economic efficiency andenvironmental impact. These activities include counseling and training for farmers onthe use environmentally friendly botanical pesticides. The discussions with farmersgroup revealed that pest infestations as brown planthoppers, whiteflies, andmealybugs, as well as diseases like stem rot and root rot, which contribute todecreased crop yields. The outreach program, involving 38 participants, successfullyimproved farmers' knowledge of pest and disease identification and control.Participants’ enthusiasm during discussion and demonstration sessions indicated theirreadiness to adopt new techniques in agricultural practices. Thus, this outreachinitiative is expected to have a positive impact on improving agricultural yields andthe well-being of the community in Tumbuh Mulia Village.